Thank you, teachers : true stories from America's teachers, our last line of defense and our first line of hope - Patterson, James, 1947-; Eversmann, Matt; Mooney, Chris (Little, Brown and Company, 2026)
"The son of a teacher himself, the world's #1 bestselling author James Patterson blows the lid off what is happening in today's schools with firsthand stories, highlighting the heroic efforts of the world's teachers."--Amazon.